Moving forward Southeast Asian perspectives on climate change and biodiversity - Sajise, Percy E. 1943-; Ticsay, Mariliza V.; Saguiguit, Gil C. (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2010)
This book discusses the impacts of climate change on biodiversity, as well as how biodiversity could enhance mitigation and adaptation approaches. It explores the two-way link between climate change and the state of biodiversity in Southeast Asia, by considering its direct impact on food security, water supply and livelihood among others. It also investigates the need for all forms of life, including human society, to adapt and survive. By drawing on the experiences and lessons shared by representatives from research and development agencies, academic institutions, donors, and other organizations; and the cross-cutting issues contributed by experts, it aims to provide insight, lessons, and perspectives on how Southeast Asia is dealing with these twin concerns.